Maturity analysis and monitoring system for sugarcane crops - Camacho, Jonathan Clark S. (Animo Repository, 2015)
The sugarcane stalk and foliage colors are strong indicators of maturity. While outdoor conditions affect the lighting of the captured sugarcane image, external factors like shadows and over exposure can easily be neglected in the Hue Saturation Value (HSV) color space. Through a series of experimentations in the HSV color space, the proponents found out that there is a significant shifting of Hue and Saturation values as sugarcane crops mature. The Hue and Saturation frequencies of both matured and not matured sugarcanes were used as data for the maturity detection comparison module which utilizes Random Forest algorithm with 90.16% accuracy. © 2015, Mechatronics and Machine Vision in Practice. All rights reserved.